(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
In this article given results of bioecological and morphological features klof the perspective varieties of soybean in the conditions of Surkhandarya region. Certain photosynthetic index (maintenances of pigments, productivity of photosynthesis) of different sorts of soy.